PENGARUH INTENSITAS PENGGUNAAN E-LEARNING TERHADAP PRESTASI AKADEMIK SISWA SMA NEGERI 1 RAMBAH SAMO KELAS XI. - Sonia; Detri Amelia Chandra; Agung Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The digital transformation in education has necessitated the adoption of technology-based learning methods, one of which is e-learning. This study aims to determine the effect of e-learning usage intensity on students’ academic achievement at SMA Negeri 1 Rambah Samo. The research employed a quantitative correlational approach, involving a population of 210 students with a purposive sample of 60 students. Data were collected through a questionnaire measuring the intensity of e-learning usage and documentation of students’ academic scores. The data were analyzed using Pearson Product Moment correlation. The results indicate a positive and significant relationship between the intensity of e-learning usage and students’ academic achievement, with a correlation value of r = 0.512 and a significance level of p = 0.000. These findings suggest that the more actively students engage with e-learning, the better their academic performance. Intensive use of e-learning also strengthens students’ self-regulated learning and higher-order thinking skills. This study recommends the structured implementation of e-learning in schools and encourages further research with broader variables and a mixed-method approach. E-learning should be optimized as a long-term learning strategy to support the quality of secondary education in the digital era.